2009
DOI: 10.1111/j.1365-3091.2009.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency cyclicity (Milankovitch and millennial‐scale) in slope‐apron carbonates: Zechstein (Upper Permian), North‐east England

Abstract: The Upper Permian (Zechstein) slope carbonates in the Roker Formation (Zechstein 2nd-cycle Carbonate) in North-east England consist of turbidites interbedded with laminated lime-mudstone. Studies of turbidite bed thickness and relative proportion of turbidites (percentage turbidites in 20 cm of section) reveal well-developed cyclicities consisting of thinning-upward and thickening-upward packages of turbidite beds. These packages are on four scales, from less than a metre, up to 50 m in thickness. Assuming tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…On the lower slope and on the toe-of slope apron calciturbidites and dolomudstones predominate (Type II; cf. Mawson and Tucker, 2009), as observed in the Gorz ow Wielkopolski2 well (Figs. 2 and 3A).…”
Section: Facies Sequence Stratigraphy and Depositional Model E Resulsupporting
confidence: 58%
“…On the lower slope and on the toe-of slope apron calciturbidites and dolomudstones predominate (Type II; cf. Mawson and Tucker, 2009), as observed in the Gorz ow Wielkopolski2 well (Figs. 2 and 3A).…”
Section: Facies Sequence Stratigraphy and Depositional Model E Resulsupporting
confidence: 58%
“…Using a similar approach, in the Eocene Ainsa basin (Spain) the accumulation of 25 turbiditic sandbodies in 10 Myr could be related to long‐period eccentricity ( ca 400 kyr) cycles (Heard et al ., ; Pickering & Bayliss, ). Finally, Mawson & Tucker () showed cyclicities in turbidite thickness and abundance in Permian carbonate slope‐apron deposits from England and suggested that they could be related to periodic fluctuations in carbonate productivity and sea‐level driven by short‐eccentricity and precession cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Strohmenger et al (1996a) reported microbial-algal carbonates from NW Germany which were deposited in sabkha, tidal flat and reefal buildup environments. Coexisting with stromatolites, algal boundstones also occur in the Danish (Clark and (after Smith, 1980;Mawson and Tucker, 2009). BS e Bakevelia Sea.…”
Section: Introductionmentioning
confidence: 93%